2022
DOI: 10.56770/jcp2021521
|View full text |Cite
|
Sign up to set email alerts
|

Gastroretentive floating microspheres for the management hypertension based on drug combination of amlodipine /losartan

Abstract: Background: Hypertension is one of the serious global health issues that affect millions of people and leads to cardiovascular damage if remain untreated. Various antihypertensive drugs have been developed but it is difficult to achieve better control of blood pressure by using mono-therapy so in this research work, combination therapy having sustained effect for the treatment of hypertension was developed. Method: Gastroretentive floating microspheres of amlodipine besylate and losartan potassium were formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…7). The presence of endothermic peaks in formulations can be observed distinctively which indicated that all components of a formulation are compatible with each other [23][24].…”
Section: Dsc Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…7). The presence of endothermic peaks in formulations can be observed distinctively which indicated that all components of a formulation are compatible with each other [23][24].…”
Section: Dsc Analysismentioning
confidence: 92%
“…The most relevant IR bands [(O-H stretching, CH3 stretching, and pyridine ring stretching vibrations] were allocated to the mirtazapine hydrochloride FT-IR and Raman experimental data with the goal of discovering the coordination effects. This study looked at mirtazapine's theoretical infrared spectrum (between 1600 and 1000 cm -1 ) [19]. The FTIR spectra of HPMC E50 have shown the specific bands of -CH 2 at 2900 cm -1 , -OH from 3500-3300 cm -1 , -CO from 1650-1600 cm -1 , methoxy group from 1500-1450 cm -1 and-C-O-C from 1300-1250 cm -1 .…”
Section: Ftir Studymentioning
confidence: 99%
“…7). The presence of endothermic peaks in formulations can be observed distinctively which indicated that all components of a formulation are compatible with each other [23][24].…”
Section: Dsc Analysismentioning
confidence: 92%
“…The most relevant IR bands [(O-H stretching, CH3 stretching, and pyridine ring stretching vibrations] were allocated to the mirtazapine hydrochloride FT-IR and Raman experimental data with the goal of discovering the coordination effects. This study looked at mirtazapine's theoretical infrared spectrum (between 1600 and 1000 cm -1 ) [19]. The FTIR spectra of HPMC E50 have shown the specific bands of -CH 2 at 2900 cm -1 , -OH from 3500-3300 cm -1 , -CO from 1650-1600 cm -1 , methoxy group from 1500-1450 cm -1 and-C-O-C from 1300-1250 cm -1 .…”
Section: Ftir Studymentioning
confidence: 99%